The Holocaust and collective memory the American experience - Novick, Peter (Bloomsbury, 1999)
How and when did the Holocaust come to loom so large in postwar Jewish and American and international life? This book sets out to answer this question. It also asks whether defining Jewishness in terms of victimhood alone does not hand Hitler a posthumous victory.